HAMBATAN INTERNALISASI NORMA PROTOKOL MAPUTO DALAM PEMENUHAN HAK PEREMPUAN DI MALAWI - Pratiwi, Tiffany Setyo; Handayani, Serli (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2025)
Malawi is one of the African Union member states that ratified the Maputo Protocol as an effort to fulfill women's human rights. This study aims to explain how the Maputo Protocol norms are internalized in Malawi through three stages: norm emergence, norm acceptance, and norm internalization. Furthermore, this study will analyze the obstacles to the implementation of the Maputo Protocol at the community level. This study uses a qualitative research method with data sources through secondary data derived from journal articles, online news, and data from official government websites. The findings of this study indicate that the internalization of the Maputo Protocol is demonstrated by Malawi's actions in formalizing the formation of new laws in 2006, namely the Law on the Prevention of Domestic Violence, the Law on Inheritance of 2011, the Law on Gender Equality of 2014, and the Constitutional Amendment Law Number 36 of 2017. Internalization is also demonstrated by the institutional governance process in the government that is oriented towards gender equality policies. However, this study found that obstacles in the internalization of the Maputo Protocol norms at the community level are still very large. These obstacles stem from the lack of public knowledge about the Maputo Protocol. More specifically, this study highlights the government's inability to legalize medical abortion as part of implementing the values of the Maputo Protocol. This situation is driven by the complexity of the conceptual frameworks of religious and cultural leaders in Malawi regarding abortion, which is considered a "grave sin", which has implications for political dynamics, where Malawi's political elite considers the opinions of religious leaders as a key basis for policy decisions.